The correlation between multi-mode ultrasonographic features of breast cancer and axillary lymph node metastasis - Xu, Shijian; Wang, Qi; Hong, Zhe (Frontiers in Oncology, 2024)
ObjectiveThis study aimed to explore the correlation between multi-mode ultrasonographic features of breast cancer and axillary lymph node metastasis.MethodA total of 196 patients with surgically confirmed breast cancer between September 2019 and December 2023 were included. Data on preoperative B-mode ultrasound (US), color Doppler, and shear wave elastography (SWE) features of breast cancer masses were collected and analyzed to determine their correlation with axillary lymph node metastasis. The area under the receiver operating characteristic curve (AUC) of B-mode US, color Doppler, SWE, and the multi-mode predictive model for evaluating axillary lymph node metastasis were compared.ResultsAmong the 196 patients, 70 had positive axillary lymph nodes, while 126 had negative axillary lymph nodes. There was no significant difference in the color features between the negative and positive axillary lymph node groups. Multifocality/multicentricity, architectural distortion, microcalcifications, and the “stiff rim” sign in SWE were identified as independent risk factors to predict axillary lymph node metastasis according to binary logistic regression analysis. The AUC of the predictive model based on these independent risk factors was 0.803 (95% CI: 0.739–0.867), which was significantly higher than that of B-mode US or SWE alone.ConclusionMultifocality/multicentricity, architectural distortion, microcalcifications, and the “stiff rim” sign in SWE were found to be valuable for predicting axillary lymph node metastasis in patients with breast cancer. The predictive model developed in this study, combining the multi-mode ultrasonographic features of breast cancer masses, could serve as a noninvasive and convenient method to predict axillary lymph node status. This approach could aid in clinical decision-making and individualized treatment to improve the prognosis of breast cancer patients.